Análise dos resultados de testes de triagem auditiva em escolares - Guerra-Silva, Paloma Luara (2012)
Introduction: Hearing screening in school is shown an important health measure since the levels of audibility interfere in the perceptions of the information by the student. However, with advent of new technologies in hearing evaluation, several tests can be applied in the hearing screening in this population. Therefore, it is important to evaluate which one has the greatest ability to detect hearing loss. Objective: To analyze the results of hearing screening in school children by means of four tests, singly and combined, aged between 4 and 12 years of age to detect hearing loss whose thresholds are higher than air 15 dBHL. Methods: They were part of this sample, 182 children of both sexes, aged between 4 and 12 years, private school students chosen for convenience in São Paulo. They performed a hearing screening by means of four tests, tympanometry (PPT> - 200 daPa), pure tone in the frequencies of 4, 2 and 1 kHz at 20 dB HL, hearing screening by transient otoacoustic emissions (TEOAE) hearing screening by distortion-product otoacoustic emissions (DPOAE). All students were tested for auditory thresholds by air performed in a soundproof booth on the same day and after four tests. The students whose levels of audibility who had level above 15 dBHL was referred for diagnostic audiological screening later date. Results: The analysis of the hearing screening with the four tests showed a failure rate of 14.8% in at least one of the tests. The analysis of the efficiency of individual tests revealed that the hearing screening test which was the tonal values of sensitivity (84.44%), specificity (98.48%), PPV (84.96%), accuracy (95.88% ) was better. For the analysis of tonal combinations hearing screening associated with TEOAE obtained 97, 22% sensitivity, specificity 95.16%, 66.61% PPV and 95.32% of the model accuracy. The evaluation of time between tests showed that the GI group (4-7 years) was presented the longest in all of them, however, TEOAE and DPOAE tests showed the shortest time and the highest tone hearing screening. The occurrence of auditory changes confirmed by the gold standard was 10.4% and the estimated prevalence of hearing loss for these children was 2.7%. Conclusion: For hearing screening in school whose purpose was to detect changes in levels of audibility if hearing screening is done by only one test, the test to be eligible tone hearing screening, if there are possibilities of combining one or more tests the combination more effective for these students was associated with tonal hearing screening TEOAE.